R17 Bacteriophage Replicase: Association with the Inhibition of Qβ, fd Bacteriophage and β-Galactosidase Production - Scott, John W. (1975)
Superinfection of Escherichia coli with amber mutants of R17 phage which produce R17 replicase inhibits production of the RNA phage Qβ, the DNA phage fd, and the host enzyme β-galactosidase. Inhibition required R17 replicase production and was related to the amount of replicase produced.